The podoplanin-CLEC-2 axis inhibits inflammation in sepsis - Julie Rayes (Nature Portfolio, 2017)
Sepsis is a life-threatening condition where exaggerated inflammatory responses lead to severe tissue damage. Here, Rayes and colleagues show that the interaction between podoplanin and its receptor CLEC-2 on platelets plays a critical role in limiting inflammation during sepsis.